Investigating Senior Secondary School Students' Beliefs about Further Mathematics in a Problem-Based Learning Context - A.O. Fatade; A.A. Arigbabu; D. Mogari; A.O.A. Awofala (University of Sofia, 2014)
The study investigated the effect of problem-based learning (PBL) on senior secondary school students' beliefs about Further Mathematics in Nigeria within the blueprint of pre-test-post-test non-equivalent control group quasi-experimental design. Intact classes were used and in all, 96 students participated in the study (42 in the experimental group taught with the PBL and 54 in the control group taught using the Traditional Method (TM)). One research instrument tagged Beliefs about Further Mathematics Questionnaire (BFMQ, Cronbach alpha (α)=.86) was developed and used for the study and data collected were analysed using the descriptive statistics of mean and standard deviation which served as precursor to testing the null hypothesis for the study using an independent samples t-test and analysis of variance. Results showed that participants held strong beliefs about further mathematics and there was a statistically significant difference in the mean post-treatment scores on BFMQ (t=-6.22, p=.000 for t-test) and (F(1,95)=38.49; p<.001 for ANOVA) between students exposed to the PBL and those exposed to the TM, in favour of the PBL group. Based on the results, the study recommended that PBL should be adopted as an instructional strategy for promoting meaningful learning in and enhancing beliefs about further mathematics and efforts should be made to integrate the philosophy of PBL into the preservice teachers' curriculum at the teacher-preparation institutions in Nigeria.